Dispute resolution in the Islamic banking industry of Tanzania: learning from other jurisdictions - Hikmany, Abdul Nasser H; Oseni, Umar Aimhanosi (Emerald Group Publishing Ltd., 2016)
This paper aims to examine the prospects of a dispute resolution framework for the Islamic banking industry in Tanzania under the existing legal framework. Design/methodology/approach: This paper is based on comparative study by drawing significant lessons from other jurisdictions, and argues that to avoid some of the initial drawbacks in the dispute resolution framework for Islamic banking transactions in more advanced jurisdictions like Malaysia and United Kingdom, it is important for Tanzania to get it right from the onset to effectively manage Islamic banking disputes. Findings: The study finds that apart from the court system which provides the main avenue for Islamic finance litigation, other processes such as arbitration and mediation which are deemed to be more sustainable could also be developed for effective dispute management. Research limitations/implications: The study focuses on Tanzania banking system with comparison to other jurisdictions. Practical implications: An increase of Sharī’ah-compliant products in Tanzania has led to the establishment of a number of Islamic banks. This study demonstrates the need for Tanzania to make use and/or make adjustment of its laws for effective dispute settlement of banking-related disputes. Originality/value: This study appears to be the first paper to draw significant experiences from other jurisdictions to resolve Islamic banking disputes in Tanzania. It is expected to provide a good policy framework for the stakeholders in the Islamic banking industry in Tanzania.